2023
DOI: 10.3389/fpls.2023.1320473
|View full text |Cite
|
Sign up to set email alerts
|

Intraspecific phylogeny and genomic resources development for an important medical plant Dioscorea nipponica, based on low-coverage whole genome sequencing data

Ke Hu,
Min Chen,
Pan Li
et al.

Abstract: Dioscorea nipponica Makino, a perennial twining herb with medicinal importance, has a disjunctive distribution in the Sino-Japanese Floristic Region. It has a long history in traditional Chinese medicine, with demonstrated efficacy against various health conditions. However, the limited genomic data and knowledge of genetic variation have hindered its comprehensive exploration, utilization and conservation. In this study, we undertook low-coverage whole genome sequencing of diverse D. nipponica accessions to d… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3

Citation Types

1
2
0

Year Published

2024
2024
2024
2024

Publication Types

Select...
2

Relationship

1
1

Authors

Journals

citations
Cited by 2 publications
(3 citation statements)
references
References 58 publications
1
2
0
Order By: Relevance
“…Significantly, the mVISTA analysis underscored that specific intergenic spacers, particularly trnK – trnQ and psbM – trnD , exhibited low sequence similarity, displaying gaps among the identified clades ( Figure 2 ). This observation, coupled with our previous studies on plastomes of D. alata ( Lu et al., 2023 ) and D. nipponica ( Hu et al., 2023b ), suggested that variations in intergenic spacers, particularly trnK – trnQ , could be contributing to the diversity in plastome sizes within individual Dioscorea species. However, further investigation is warranted to comprehensively understand these variations.…”
Section: Discussionsupporting
confidence: 72%
See 2 more Smart Citations
“…Significantly, the mVISTA analysis underscored that specific intergenic spacers, particularly trnK – trnQ and psbM – trnD , exhibited low sequence similarity, displaying gaps among the identified clades ( Figure 2 ). This observation, coupled with our previous studies on plastomes of D. alata ( Lu et al., 2023 ) and D. nipponica ( Hu et al., 2023b ), suggested that variations in intergenic spacers, particularly trnK – trnQ , could be contributing to the diversity in plastome sizes within individual Dioscorea species. However, further investigation is warranted to comprehensively understand these variations.…”
Section: Discussionsupporting
confidence: 72%
“…Enantiophyllum ( Lu et al., 2023 ). Notably, regions like three intergenic spacers ( rps16 – trnQ , trnE – trnT , and trnL – rpl32 ) and two intron regions (intron 1 of clpP and intron trnG ) promised substantial insights into assessing intraspecific genetic variability of D. nipponica ( Hu et al., 2023b ). Given these findings, further exploration of molecular markers, particularly in non-coding regions, becomes imperative in Dioscorea species.…”
Section: Discussionmentioning
confidence: 99%
See 1 more Smart Citation